Neoadjuvant radiotherapy in rectal cancer – less is more?. (20th October 2019) - Jootun, N.; Sengupta, S.; Cunningham, C.; Charlton, P.; Betts, M.; Weaver, A.; Jacobs, C.; Hompes, R.; Muirhead, R.
Abstract: Aim: There is significant international variation in the use of neoadjuvant radiation prior to total mesorectal excision. The MERCURY group advocate selective neoadjuvant chemoradiotherapy (CRT). We have performed a retrospective, single‐centre study of patients treated with CRT, where only the circumferential resection margin is threatened, with the aim of identifying whether a more selective approach to CRT provides acceptable local relapse rates (LRRs). Method: All consecutive patients who underwent radical surgery for rectal adenocarcinoma over a 5‐year period (2007–2012) in the Oxford University Trust were considered. Electronic hospital systems were reviewed to obtain patient and tumour demographics, treatment and follow‐up information. All patients were classified into risk categories according to National Institute for Health and Care Excellence guidance. Data were analysed using Microsoft Excel and R. Results: Two hundred and seventy‐two patients were identified: 123, 89 and 60 in the high‐, intermediate‐ and low‐risk categories, respectively. Seventy‐nine per cent of those in the high‐risk group, 6% in the intermediate and 5% in the low‐risk group underwent CRT. The overall 5‐year LRR and distant recurrence rate (DRR) were 5.2% and 17.8%, respectively. The 5‐year LRR for those who went straight to surgery was 2.0% and for those who had neoadjuvant CRT it was 7.4%. The DRR for these two groups was 8.5% and 18.9%, respectively. Conclusion: Our series demonstrates that the use of CRT only in margin‐threatening tumours, results in an exceptionally low LRR for those without margin‐threatening disease. In routine clinical care, this strategy can minimize the significant morbidity of multimodal treatment and allow earlier introduction of systemic therapy to minimize distant recurrence.